A Qualitative Study on Practices and Issues of Blended Learning in Higher Education: Irshad Hussain, Abid Hussain Shahzad,Rafaquat Ali (PJDOL, 2023)
This qualitative study explored the practices and issues related to blended learning in university. It adopted purposive-cum convenient sampling technique. The researchers collected qualitative data from 30 university teachers and 60 undergraduate students through focused group interviews. The researchers did thematic analysis of the data keeping in view objectives of the study. It demonstrated that university academia and undergraduate students use online resources in support of face-to-face instruction.